Correlation of retinal layer changes with vision gain in diabetic macular edema during conbercept treatment - Xu, Yupeng (BMC Ophthalmol, 2019)
BACKGROUNDS: To assess the changes in individual retinal layer thickness and visual function associated with gains in visual acuity after an intravitreal conbercept injection in the diabetic macular edema (DME) on spectral domain optical coherence tomography (SD-OCT) and microperimetry during 1-year follow-up. METHODS: Retrospective observational study. Twenty patients with clinically significant DME in the study eye were imaged by SD-OCT every 3 months and MP1 microperimeter in the third month while receiving anti-vascular endothelial growth factor (VEGF) (conbercept) treatment. In each patient, seven retinal layers were segmented in 98 scans covering a 6 mm × 6 mm area of the macula at baseline and during 1 year of treatment. An automatic, full-threshold microperimetry of the central field (10° × 10°, 40 stimulated points) with the MP1 microperimeter. Thickness and microperimetry changes were quantitatively measured and evaluated for their correlation with increases in visual acuity. RESULTS: Although thicknesses of the inner nuclear layer (INL) and the outer nuclear layer (ONL) were reduced the most after treatment (p < 0.05), decreases of the ganglion cell layer (GCL) (r = 0.591, p = 0.006) and inner plexiform layer (IPL) (r = 0.663, p = 0.001) in central subfield area was associated with best-corrected visual acuity (BCVA) gain, and had the best estimation of BCVA gain (adjust R(2) = 0.544). Mean macular sensitivity in the central subfield was also well correlated with BCVA gain (r = 0.531, p = 0.016). CONCLUSIONS: Neural recovery occurred after the resolution of edema during conbercept treatment, due to the decreases in GCL and IPL associating with gains in vision and improved microperimetry. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12886-019-1131-0) contains supplementary material, which is available to authorized users.